Advanced contrast nanoagents for photoacoustic molecular imaging, cytometry, blood test and photothermal theranostics - de la Zerda, Adam; Kim, Jin-Woo; Galanzha, Ekaterina I; Gambhir, Sanjiv S; Zharov, Vladimir P (Contrast media and molecular imaging, 2011)
Various nanoparticles have raised significant interest over the past decades for their unique physical and optical properties and biological utilities. Here we summarize the vast applications of advanced nanoparticles with a focus on carbon nanotube (CNT)-based or CNT-catalyzed contrast agents for photoacoustic (PA) imaging, cytometry and theranostics applications based on the photothermal (PT) effect. We briefly review the safety and potential toxicity of the PA/PT contrast nanoagents, while showing how the physical properties as well as multiple biological coatings change their toxicity profiles and contrasts. We provide general guidelines needed for the validation of a new molecular imaging agent in living subjects, and exemplify these guidelines with single-walled CNTs targeted to α(v) β(3) , an integrin associated with tumor angiogenesis, and golden carbon nanotubes targeted to LYVE-1, endothelial lymphatic receptors. An extensive review of the potential applications of advanced contrast agents is provided, including imaging of static targets such as tumor angiogenesis receptors, in vivo cytometry of dynamic targets such as circulating tumor cells and nanoparticles in blood, lymph, bones and plants, methods to enhance the PA and PT effects with transient and stationary bubble conjugates, PT/PA Raman imaging and multispectral histology. Finally, theranostic applications are reviewed, including the nanophotothermolysis of individual tumor cells and bacteria with clustered nanoparticles, nanothrombolysis of blood clots, detection and purging metastasis in sentinel lymph nodes, spectral hole burning and multiplex therapy with ultrasharp rainbow nanoparticles.